PS 05-16 AUTONOMIC DYSFUNCTION IN HOME BLOOD PRESSURE MONITORING: ITS RELATIONSHIP WITH ARTERIAL STIFFNESS AND SUBCLINICAL ATHEROSCLEROSIS. (September 2016) - Kempny, Pablo; Gonzalez, Sergio; Svane, Jorge Chiabaut; Inserra, Felipe; Schiavone, Maximo
Abstract : Objective: a) To evaluate the association between autonomic dysfunction (increased blood pressure [BP] variability and decreased heart rate [HR] variability) and vascular function. b) Determine whether autonomic dysfunction is associated with presence of carotid plaques. Design and Method: We evaluated 311 consecutive subjects who attended to the Cardiometabolic Unit, Cardiology Departament, Austral University Hospital. All patients underwent anthropometric measurements. BP and HR were recorded through home BP monitoring/ 7 consecutive days (MicroLife, ESH). Pulse wave velocity (PWV) and augmentation index 75 (Aix75) were carried out using an oscillometric device (Mobil-O-Graph) at rest. Carotid arteries (common, bulb and external/internal proximal territories) and bifurcations of femoral arteries were scanned through a carotid ultrasound to determine the presence of plaques. An index of autonomic dysfunction (standard deviation of systolic BP/standard deviation of HR) was defined (AD index, ADI). ADI deciles were determined. The population was classified by deciles of ADI. Levels of PWV and Aix75 were determined by ADI deciles (ANOVA). The interactions between presence of atherosclerotic plaque and ADI deciles were performed (Chi 2 for trend). Results: After applying exclusion criteria 280 subjects (132 ± 14/88 ± 11 mmHg, 53 +/-10 years, 71% male) were included. The subjects with the highest ADI (9 th – 10 th deciles) presented a higher PWV (p < 0.001). Aix75 showed a progressive increment with ADI deciles (p = 0.056). The increments in magnitude of ADI were related with higher risk of having atherosclerotic plaques, with a considerable trend toward significance (p = 0.062). Conclusions: The alterations in blood pressure and heart rate homeostasis presented a positive relationship with PWV, and marginally associations with aortic augmentation and subclinical atherosclerosis, which could indicate some role of mid-term autonomic dysfunction in early vascular damage.